Identification and Quantification of Staphylococcus Aureus in Saliva at Different Time Intervals Among Dental Personnel Wearing Surgical Masks During Sars Cov2- A Prospective Observational Study: Life Sciences-Spondylolisthesis - NS, Arungani; A, Santha Devy; R, Suganya; S, Uma Devi; M, Sivaramakriashnan; S, Vidyalakshmi (International Journal of Life Science and Pharma Research, 2022)
Our world combats the rapid spread of Covid 19 by wearing face masks which have become the norm. But it’s effect on oral microbiome is yet to be studied. Staphylococcus aureus is the leading cause of bacterial co-infection in Covid-19-affected patients worsening their prognosis. Dislodgement of this bacterium from the oral cavity is said to cause many systemic diseases. As dentists are more prone to an aerosolic environment and a potential source of cross-contamination, we intended to identify and quantify S. aureus in the saliva of dental personnel wearing surgical masks. Unstimulated whole saliva samples of 120 healthy dental professionals wearing surgical masks were cultured for S. aureus growth in Mannitol Salt Agar medium for 48 hours at 37°C. After 1 hour and 6 hours of mask usage, the number of colony-forming units counted. After 1 hour and 6 hours of mask usage, 56% and 52.5% demonstrated growth of S. aureus respectively. There was a statistically significant mean reduction of 1.61*103 colony forming units after 6 hours of mask usage. There is a reduction in the prevalence and number of colony-forming units of S. aureus in the unstimulated saliva of healthy dental professionals after 1 hour and 6 hours of surgical mask use. As a result, mask use not only controls the spread of Covid but may also aid in reducing the source and spread of S. aureus cross infection, lowering the risk of morbidity and mortality in diseased patients.